MENELISIK KOSMOPOLITANISME SASTRA ARAB (Kajian Sastra Banding) - Tatik Maryatut Tasnimah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2010)
To exist, a cosmopolitan literary movement is a must for a national literature. This means that the national literature must consider the entire humankind as more meaningful than its group, region or state. Cosmopolitanism views all races and all continents with the same human interest and concern. In additions, two consequences come up with, the influenced literature and/or the influencing literature. As a dynamic organism, Arabic literature has been cosmopolitanizing itself especially since its reviving age back in the end of 18th century and in the first quarter of 19 century. New genres, themes, styles, theories as well as criticisms have been adopted. By doing so, Arabic literature has come to the same level as other literary cannons in the world. In turn, cosmopolitanism of Arabic literature nourishes the comparative literary study.